Orthogonal wave superposition of wrinkled, plasma-oxidised, polydimethylsiloxane surfaces. Issue 3 (28th November 2019) - Pellegrino, Luca; Khodaparast, Sepideh; Cabral, João T.
Abstract : We report a versatile approach to generate 2D dual-frequency patterns on soft substrates by superposition of 1D single-frequency wrinkles. Abstract : We report a versatile approach to generate 2D dual-frequency patterns on soft substrates by superposition of 1D single-frequency wrinkles. Wave superposition is achieved by applying sequential orthogonal strains to elastomeric coupons, as opposed to the application of a (simultaneous) biaxial strain field. First, a 1D wrinkling pattern is induced by the well-known mechanical instability of a bilayer formed by oxygen plasma-oxidation of a (pre-strained) polydimethylsiloxane elastomer. The wrinkled surface formed upon strain release is then replicated to obtain a stress-free substrate, and stretched in the direction perpendicular to the first generation. Subsequent plasma exposure and mechanical relaxation (with independent process parameters) yield a prescribed second-generation wrinkling, whose profile and dependence on the first generation we examine in detail. By independently varying plasma oxidation and strain parameters in both directions, we demonstrate the formation of a wide array of topographies, including arrays of symmetric 2D checkerboard patterns with exceptional area coverage with respect to those formed by simultaneous 2D wrinkling. While the resulting topographies cannot be explained in terms of a simple orthogonal wave superposition, we show that, by accounting for the orthogonal prestrain experienced by the first wrinkling generation, the resulting 2D patterns can be readily calculated from 1D wrinkling behaviour.